Factors Affecting Research and Extension Linkage in Veterinary Universities in India - Sinha, Sushil K; Chander, Mahesh; Verma, Med R; Jena, Anupama (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The effective research-extension linkage in agriculture and veterinary universities depends on multiple factors. To analyze such factors,  the present study was carried out with a sample of 80 researchers and 40 extensionists from four veterinary universities in India. The  correlation and regression analysis revealed that most of the dimensions of functional R-E linkage were less affected by the selected  profile characteristics of respondents. Their information accessibility, job-experience, training/seminar familiarity and perception of  management have a positive and significant relationship with linkage strength. So, these factors should be addressed by the university  to strengthen and design effective linkage strategies for research and extension.
Keywords: Correlation-regression; Research-extension linkage; Veterinary University